Performance evaluation of five ELISA kits for detecting anti-SARS-COV-2 IgG antibodies - Hadi M., Yassine (2020)
ObjectivesTo evaluate and compare the performances of five commercial ELISA assays (EDI, AnshLabs, Dia.Pro, NovaTec, and Lionex) for detecting anti-SARS-CoV-2 IgG. Methods70 negative control samples (collected before the COVID-19 pandemic) and samples from 101 RT-PCR-confirmed SARS-CoV-2 patients (collected at different time points from symptoms onset: ≤7, 8-14, and >14 days) were used to compare the sensitivity, specificity, agreement, positive and negative predictive values of each assay with RT-PCR. A concordance assessment between the five assays was also conducted. Cross-reactivity with other HCoV, non-HCoV respiratory viruses, non-respiratory viruses, and nuclear antigens was investigated. ResultsLionex showed the highest specificity (98.6%, 95%CI: 92.3-99.8), followed by EDI and Dia.Pro (97.1%, 95%CI: 90.2-99.2), NovaTec (85.7%, 95%CI: 75.7-92.1), then AnshLabs (75.7%, 95%CI: 64.5-84.2). All ELISA kits cross-reacted with one anti-MERS IgG positive sample except Lionex. The sensitivity was low during the early stages of the disease but improved over time. After 14 days from symptoms onset, Lionex and NovaTec showed the highest sensitivity at 87.9% (95%CI: 72.7-95.2) and 86.4% (95%CI: 78.5-91.7), respectively. The agreement with RT-PCR results based on Cohen’s kappa was as follows: Lionex (0.89)> NovaTec (0.70)> Dia.Pro (0.69)> AnshLabs (0.63)> EDI (0.55). ConclusionThe Lionex ELISA, which measures antibodies solely to the S1 protein, demonstrated the best performance.